Implementation and evaluation of a low-cost and compact electrodermal activity measurement system. (October 2016) - Schmidt, M.; Penner, D.; Burkl, A.; Stojanovic, R.; Schümann, T.; Beckerle, P.
Highlights: A low-cost electrodermal measurement system is implemented and evaluated. Appropriate resolution by amplifying electrodermal level and response individually. Mobile application is feasible due to small footprint of the implementation. Comparison to a commercial product suggests applicability for psychological studies. Accessible presentation of design facilitates simple recreation of the system. Abstract: In psychological research, acquiring information about mental excitement or central nervous activity is fundamental for assessment. Such information can be used as a psychological measure in various investigations like the embodiment of technical artifacts, e.g., in terms of tool use or human–machine systems. A promising method is measuring a subject's electrodermal activity (EDA), i.e., acquiring information about skin conductance or resistance. However, most commercially available measurement systems are expensive and/or not mobile. The system presented in this paper uses low-cost components, has a small footprint, and is easy to rebuilt for scientific applications. It measures EDA by applying a constant voltage and achieves reasonable resolution by individually amplifying slow and fast electrodermal effects, i.e., level and response. Based on a design from the literature, the paper explains the functionality, extensions, and implementation of the system. A comparative study with a commercial laboratory system is conducted and discussed: although the presented system offers a lower resolution, the quality of the recorded data is deemed sufficient for psychological studies.